Differences In Stock Trade Frequency Due To Announcement Of Large-Scale Social Restrictions (Psbb) Due To Covid-19 In Transportation Companies Listed On The Indonesia Stock Exchange - yuliza, arma (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
The aim of this research is to find out whether there is a difference in the trading frequency of transportation companies before and after information regarding the announcement of Large-Scale Social Restrictions (PSBB). The population of this research is all transportation companies listed on the Indonesia Stock Exchange for the 2020 period. The sampling technique uses the purposive sampling method. The test equipment used in this research is the Paired Sampe Test T-Test. The research results show that there is a significant difference in trading frequency between before and after information regarding the announcement of Large-Scale Social Restrictions (PSBB).